Additive manufacturing as a platform for introducing cyber-physical services - Khajavi, Siavash H. (2018)
Additive manufacturing (AM) is increasingly used for the production of functional components. This process is based on digital design model and can produce customized components with no additional cost (toolless process). AM is an inherently model-centric approach to manufacturing which provides a starting point for extending product-centric control and services to tasks and operations beyond manufacturing. In this paper, we investigate a method to assign a unique identification to each part using AM and the additional product-centric services enabled through it, are discussed. The use of a unique identifier in the form of ID@URI which is additively manufactured (from the design file) on the parts enables additional services throughout the parts' lifecycle. Assembly, delivery, aftersales services, and maintenance, as well as product improvement, are the major product-centric services benefiting from identification introduced through the use of AM.